Kemitraan Pemerintah-Swasta dan Relevansi Terhadap Reformasi Administrasi Negara - Dwiyanto, Agus (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 1996)
The economic crisis which was experienced by the government of Indonesia in the 1980s has a very significant implication of the reformation of state administration in Indonesia. This crisis signaled to the government dun development and public services which are exclusively dependent of government bureaucracy are very susceptible to the global economiclOrces. Al the end of it it is reaaayl that oilier actors outside the state bureaucracy are absolute necessisary for instance. the private and the voluntag agents as a support in the process of development and also us participants in providing public services. Because of this therefore, cooperation between these three actors is voy desirable in order That an efficient model of the provision of public services to the community can be achieved. One of the concepts which is advanced in this writing is the development of partnership between the state and the private sector in providing public services. The success in eslablismeni of this partnership is in itself very much influenced by : the change in attitude and orientation of the bureaucrats. extending opporumiol it the private and the LSM agents to develop through revision of the constitution which limits their role in taking care of public services, the necessity of government limitation in providing public services whenever the private and the LSM agents have been able to act. the shift in the role of government towards the private institutions which is desirable that it is done with transparency and openness. and finall is the necessity for effectiveness in bureaucratic control and politicians who are increasingly widening the role of the private agens to participate.